2017
DOI: 10.1111/dom.12983
|View full text |Cite
|
Sign up to set email alerts
|

Safety of sitagliptin in patients with type 2 diabetes and chronic kidney disease: outcomes from TECOS

Abstract: Participants in TECOS with CKD had higher incidences of serious adverse events and diabetes complications than those without CKD. Treatment with sitagliptin was generally well tolerated, with no meaningful differences in safety outcomes observed between those with CKD assigned to sitagliptin or placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 11 publications
2
15
1
3
Order By: Relevance
“…Moreover, there was no impact of sitagliptin or vildagliptin on GFR, even when renal function was already moderately/severely impaired. Likewise, in the longer duration CV safety outcome studies, neither alogliptin nor saxagliptin had any effect on GFR compared to placebo, while in TECOS, although GFR was modestly lower in the sitagliptin arm, the rate of decline was similar in both arms of the trial as a whole (but interestingly, a sub‐group analysis revealed no decline in GFR in the sitagliptin cohort with CKD in TECOS). Of note, a recent mechanistic study has reported that, compared with placebo, acute and chronic (1 month) DPP‐4 inhibition with sitagliptin in patients with T2DM stimulated natriuresis in the distal, rather than the proximal, tubule, via a mechanism said to involve enhancement of levels of SDF‐1α, in line with some of the animal data mentioned above .…”
Section: Renal Safetysupporting
confidence: 73%
See 1 more Smart Citation
“…Moreover, there was no impact of sitagliptin or vildagliptin on GFR, even when renal function was already moderately/severely impaired. Likewise, in the longer duration CV safety outcome studies, neither alogliptin nor saxagliptin had any effect on GFR compared to placebo, while in TECOS, although GFR was modestly lower in the sitagliptin arm, the rate of decline was similar in both arms of the trial as a whole (but interestingly, a sub‐group analysis revealed no decline in GFR in the sitagliptin cohort with CKD in TECOS). Of note, a recent mechanistic study has reported that, compared with placebo, acute and chronic (1 month) DPP‐4 inhibition with sitagliptin in patients with T2DM stimulated natriuresis in the distal, rather than the proximal, tubule, via a mechanism said to involve enhancement of levels of SDF‐1α, in line with some of the animal data mentioned above .…”
Section: Renal Safetysupporting
confidence: 73%
“…The large CV safety outcome studies also included large numbers of patients with impaired renal function, and analyses of the cohorts with chronic kidney disease (CKD) in TECOS and SAVOR-TIMI clearly showed a correlation between poorer renal function and increasing numbers of CV, renal and hypoglycaemic events, as expected. [48][49][50] However, with the exception of hospitalization for heart failure in SAVOR-TIMI (which was higher in the saxagliptin arm), overall event rates in the CKD cohort, although greater in number, were generally not different between the DPP-4 inhibitor and the placebo arms of the trials, 48,50 reflecting the findings in the trial populations as a whole, 9,11 and indicating that the presence of kidney disease per se did not differentially influence outcomes in the 2 arms of the trials. Moreover, a specific analysis of renal events in SAVOR-TIMI revealed no adverse effects of DPP-4 inhibition with saxagliptin on renal safety outcomes.…”
Section: Heart Failurementioning
confidence: 99%
“…Sitagliptin, predominantly (in up to 90%) excreted with urine as an active drug, accumulates in CKD. Despite precautions suggested by the manufacturer for CKD patients, the drug was generally well tolerated and effective in improving metabolic control of T2D also in this patient group [36]. Vildagliptine is also safe and effective in CKD patients, despite the fact that the drug is metabolised by the kidneys and excreted with urine.…”
Section: Dpp4 Inhibitorsmentioning
confidence: 78%
“…It has been suggested that inhibiting these additional pathways may lead to beneficial outcomes, such as improved diabetic wound healing via SDF-1 inhibition [14]. Prior to CARMELINA, CVOTs had been reported for three DPP-4 inhibitors approved for clinical use in the European Union: saxagliptin [15], alogliptin [16,17] and sitagliptin [18][19][20]. Safety was uniformly demonstrated across the class for atherosclerotic CV outcomes, with a neutral effect on major adverse CV event (MACE) outcomes for all three agents [1] ( Table 1).…”
Section: 2mentioning
confidence: 99%
“…2B). A limitation of these CVOTs has been that only a minority of patients in the study cohorts had reduced renal function at baseline [1,19] (Fig. 3A), while renal outcomes were usually only assessed as exploratory or post hoc analyses [15][16][17][18][19][20].…”
Section: 2mentioning
confidence: 99%